An Analysis of Energy Production of Rooftop on Grid Solar Power Plant on A Government Building (A Case Study of Setjen KESDM Building Jakarta) - Zulkifli Zulkifli; Wahyu Wilopo; Mohammad Kholid Ridwan (JPSE (Journal of Physical Science and Engineering), 2019)
In producing electrical energy, the solar module is affected by some factors, such as the solar radiation intensity, temperature, orientation and slope of the module, and shading that occurs during operation. The solar power plant of Setjen KESDM is coordinated at 6°10’53.73” south latitude and 106°49’24.61” east longitude, with a slope of 9.7°–10.0° and azimuth of -2.0° to -5.0° towards the north. It consists of five placement locations, including 11th floor rooftop, T1, T2, T3, and L carports with a total capacity of 150 kWp. The analysis of the production of rooftop on grid solar power plant in the government building with a case study in the Setjen KESDM was intended to determine the level of production of the solar power plant built and the parameters that influence it, which was conducted by comparing the real results with the simulation results using SAM software. The energy production in 2017 was 118,259.3 kWh, in 2018 was 106,318.3 kWh, and in 2019 was 109,973.0 kWh. The highest production was obtained in September, October, and March every year due to the maximum solar radiation. The solar power plant on the 11th floor rooftop was more maximal in producing energy for all positions of the sun than the solar power plant on the T1, T2, T3, and L carports because it was free of shading from buildings and trees. The output produced by the solar power plant of Setjen KESDM could not reach the maximum point because the location temperature was higher than the standard test conditions of the solar module. DOI: http://dx.doi.org/10.17977/um024v4i22019p055